PENGARUH JARAK TANAM DAN VARIASI WAKTU PENYIANGAN GULMA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH KERITING VARIETAS KENCANA - Meiliasari, Lisna Suci; Romdhonah, Yayu; Ritawati, Sri; Saylendra, Andree (Leuit (Journal of Local Food Security), 2023)
The purpose of this study was to determine the effect of plant spacing and variation of weeding time on the growth and yield of curly red chili varieties of Kencana (C.annuum). This research was conducted at IP2TP Balitsa Serpong from May to September 2022. The experiment used a randomized block design (RBD) with 2 factors. The first factor was plant spacing (J) which consisted of 2 levels, namely J1 (50 cm x 50 cm), and J2 (50 cm x 60 cm). The second factor was weeding time (P) which consists of 5 levels, namely P0 - (With Weeds), P0 + (Without Weeds), P1 20 Days After Planting (DAP), P2 40 DAP, P3 60 DAP. Parameters observed included plant height (cm), number of leaves (strands), stem diameter (cm), fruit length (cm), fruit diameter (mm), number of fruit (fruit), fruit weight (g), number of fruit per plot (fruit), and fruit weight per plot (g). The J2 treatment gave the best results on the growth and yield of the Kencana variety but did not give the best results at 28 DAP, 1st harvest fruit diameter, and 3rd harvest fruit weight. The J2 treatment also gave the best results on the growth and yield of the Kencana variety but did not give the best results at 28 DAP, 1st harvest fruit diameter, and 3rd harvest fruit weight. The combination of plant spacing of 50 cm x 60 cm and weeding time of 60 DAP gave the highest average fruit length, which was classified as no 2 quality according to SNI.